Early detection and early intervention in prison: improving outcomes and reducing prison returns. Issue 1 (2nd January 2017) - Evans, Clare; Forrester, Andrew; Jarrett, Manuela; Huddy, Vyv; Campbell, Catherine A.; Byrne, Majella; Craig, Thomas; Valmaggia, Lucia
Abstract: Our aim was to investigate whether early detection was feasible in prison and whether it could improve mental health outcomes in young prisoners. A secondary aim was to explore whether it can reduce returns to prison. Between 2011 and 2014, a total of 2115 young prisoners were screened, 94 (4.4%) met criteria for ultra-high risk for psychosis and were offered an intervention, 52 actually received it. Return to prison data were sought on the 52 participants, receiving a formal intervention. Of the 52 prisoners who received an intervention, 30.8% returned to custody compared to national average reconviction rates of between 45.4 and 66.5%. Our results suggest that early detection is a feasible option in a prison setting, improving mental health outcomes and reducing returns to prison. Mental health outcomes were recorded for a sub-sample of those receiving the intervention. The results indicated statistically significant improvements on measures of depression, anxiety and psychological distress.